Some Like It Fat: Comparative Ultrastructure of the Embryo in Two Demosponges of the Genus Mycale (Order Poecilosclerida) from Antarctica and the Caribbean - Riesgo, Ana; Taboada, Sergio; Sánchez-Vila, Laura; Solà, Joan; Bertran, Andrea; Avila, Conxita (PLOS ONE, 2015)
During embryogenesis, organisms with lecithotrophic indirect development usually accumulate large quantities of energetic reserves in the form of yolk that are necessary for larval survival. Since all sponges have lecithotrophic development, yolk formation is an ineludible step of their embryogenesis. Sponge yolk platelets have a wide range of morphological forms, from entirely lipid or protein platelets to a combined platelet showing both lipids and proteins and even glycogen. So far, there are no comparative studies on the nature and content of yolk in congeneric species of sponges inhabiting contrasting environments, which could have putative effects on the larval adaptation to environmental conditions. Here, we have taken advantage of the worldwide distribution of the sponge genus Mycale, in order to compare the embryogenesis and yolk formation in two species inhabiting contrasting latitudinal areas: M. acerata from Antarctic waters and M. laevis from the Caribbean. We have compared their brooded embryos and larvae using scanning and transmission electron microscopy, and calculated their energetic signatures based on the nature of their yolk. While the general morphological feature of embryos and larvae of both species were very similar, the main difference resided in the yolk nature. The Antarctic species, M. acerata, showed exclusively lipid yolk, whereas the Caribbean species, M. laevis, showed combined platelets of lipids and proteins and less frequently protein yolk platelets. The larvae of M. acerata were estimated to possess a two-fold energetic signature compared to that of M. laevis, which may have important ecological implications for their survival and for maintaining large population densities in the cold waters of the Southern Ocean.